The management of vascular access in therapeutic apheresis - JIANG Ying; ZHUANG Yuan; YU Yang (Zhongguo shuxue zazhi)
Therapeutic apheresis (TA) is currently used for both hematological and non-hematological diseases. Due to its reliable efficacy, good safety, and simple operation, TA has been widely used in the clinical diagnosis and treatment of patients with refractory and severe diseases. From the operator's perspective, the successful completion of treatment largely depends on the appropriate vascular access. This review summarizes the background, development trends, types, advantages and disadvantages of vascular access during the TA process to guide clinical operation practice.